Apolipoprotein and lipid abnormalities in chronic liver failure - Spósito,A.C. (1997)
Total serum lipids, as well as apolipoproteins A-I (apo A-I) and B (apo B), were determined in 74 patients with chronic liver failure without cholestasis and in 82 normal subjects. The VLDL, LDL and HDL lipid fractions were reduced in the liver failure group by 36%, 24% and 46%, respectively (P<0.001). Apolipoproteins A-I and B were also reduced by 26% and 25%, respectively (P<0.001). However, the reduction of HDL cholesterol (HDLc) was more pronounced than that of apo A-I and the HDLc:apo A-I ratio was significantly lower in the liver failure group. After separating these patients into groups with plasma albumin lower than 3.0, between 3.0 and 3.5, and higher than 3.5 g/dl, the HDLc:apo A-I ratio was proportional to plasma albumin, but the correlation was not statistically significant. When these patients were separated by the Child classification of liver function, there was a correlation between the HDLc:apo A-I ratio and liver function. The differences in the HDLc:apo A-I ratio between the Child groups B and C, and A and C were statistically significant (P<0.05). We conclude that there is a more pronounced reduction in HDL cholesterol than in apo A-I in liver failure patients. Therefore, the HDLc:apo A-I ratio is a marker of liver function, probably because there is a decreased lecithin-cholesterol acyltransferase production by the diseased liver